Fabrication of hydrophobic/hydrophilic bifunctional adsorbent for the removal of sulfamethoxazole and bisphenol A in Water. Issue 5 (October 2020) - Zhou, Aijiao; Wu, Xumeng; Chen, Wangwei; Liao, Lei; Xie, Pengchao
Graphical abstract: Highlights: Hydrophobic/hydrophilic bifunctional adsorbent beads were synthesized. Good adsorption capacity for both sulfamethoxazole and bisphenol A was achieved. The adsorption kinetics were comprehensively studied. The adsorbent exhibited excellent reusability. Abstract: Powdered activated carbon embedded chitosan-polyvinyl alcohol composite (PAC/CS/PVA) beads were designed via a simple method for the adsorptive removal of hydrophilic sulfamethoxazole (SMX) and hydrophobic bisphenol A (BPA) from water. The as-prepared hydrogel was characterized, and the adsorption performances were comprehensively investigated. The maximum adsorption capacities of SMX and BPA on the adsorbent are 9.1 mg g −1 and 64.6 mg g −1, respectively. The optimal pH was around 4 for SMX and 2–9 for BPA, respectively. Higher adsorbent dosages benefited the removal efficiencies but lowered the adsorption capacities. Both temperature and ionic strength slightly affect the adsorption of SMX and BPA. Pseudo-second-order model can well describe the adsorption of SMX and BPA on the hydrogel through spontaneous and endothermic process. Langmuir isotherm model performed better than Freundlich model to fit the equilibrium data. The stable adsorption capacities of SMX and BPA after used the hydrogel for 5 cycles evidenced its excellent reusability. The high adsorption capacities (> 7 mg g −1 for SMX, > 50 mg g −1 for BPA) in the presence of typical water matrices including Cl −, SO4 2−, Cu 2+ and humic acid further suggest the good application potential of the fabricated PAC/CS/PVA beads.